1999
DOI: 10.1097/00005131-199902000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Healing Process in Open Osteotomy Model and Closed Fracture Model

Abstract: Investigators should consider the difference between the closed fracture and open osteotomy models when selecting an animal model to investigate fracture healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 16 publications
0
48
0
1
Order By: Relevance
“…In contrast, an open osteotomy stabilized with an external fixator can lead to a delayed healing due to soft tissue trauma being induced by the surgical approach. 17 However, it has advantages: the osteotomy can be created in a standardized way; external fixators provide better control of the fixation stability, especially under torsion and shear loading (important as both rotational instability and shear movements in particular hamper fracture healing 9,18 ); and an external fixator is fitted to the bone at some distance from the fracture gap, and, therefore, does not compromise the healing process. Previously, a reliable external device allowing the investigation of the influence of different mechanical conditions on fracture healing in mice was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an open osteotomy stabilized with an external fixator can lead to a delayed healing due to soft tissue trauma being induced by the surgical approach. 17 However, it has advantages: the osteotomy can be created in a standardized way; external fixators provide better control of the fixation stability, especially under torsion and shear loading (important as both rotational instability and shear movements in particular hamper fracture healing 9,18 ); and an external fixator is fitted to the bone at some distance from the fracture gap, and, therefore, does not compromise the healing process. Previously, a reliable external device allowing the investigation of the influence of different mechanical conditions on fracture healing in mice was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In a rabbit tibial fracture model, oblique fractures with a sliding fixator developed more callus and had a larger torsional rigidity than transverse fractures with an axial motion fixator [26]. However, it is difficult to determine if the outcome is due to the difference in strain magnitude or type (axiahhear).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a contributory factor may be the use of the intramedullary stabilisation technique. The development of delayed healing after tibial osteotomy in direct comparison to the closed fracture technique was previously documented in a rabbit model by Park et al [11] using an external fixator for stabilization of the bone defect. These authors showed respective differences two weeks post bone defect, but these had disappeared at later observation time points.…”
Section: Discussionmentioning
confidence: 87%